Cerebral venous thrombosis in polycythemia rubra vera: a rare case report - A., Lokesh Kumar; S., Devipriya; Hanumanram, Gowtham; M., Jagadeesan (International Journal of Advances in Medicine, 2023)
Polycythemia rubra vera (PV) is a disease characterised by increased production of red blood cells due to genetic mutation which leads to increase in RBC mass and increased viscocity of blood. Myeloproliferative neoplasms have been implicated in the causation of cerebral venous thrombosis (CVT). Here we presented a 34 year old male who present with headache and diplopia. Fundus examination revealed bilateral papilledema. MRI brain with venogram was done which revealed right transverse and sigmoid sinus thrombosis. Blood investigations revealed polycythemia, elevated RBC counts and hematocrit levels. Peripheral smear showed increased RBC, WBC and platelets. Serum erythropoietin was low. Bone marrow aspiration study revealed hypercellular marrow. Patient tested positive for JAK2 V617F mutation. Patient was treated with anticoagulants, therapeutic phlebotomy and other supportive measures. Here we present a rare case of PV presenting with CVT.